On the occasion of world kidney day 2017; obesity and its relationship with chronic kidney disease - Leila Mahmoodnia; Mohammad Reza Tamadon (Society of Diabetic Nephropathy Prevention, 2017)
Context: Numerous studies have reported the impact of obesity in the incidence of chronic kidney disease (CKD). Some studies have suggested the direct role of obesity in the incidence of CKD, while some other studies suggest an indirect effect caused by the effects of obesity on blood pressure and diabetes. Evidence Acquisition: PubMed, EBSCO, Web of Science, directory of open access journals (DOAJ), EMBASE, and Google Scholar have been searched. Results: Recent studies have presented more strong evidences on the role of obesity on the incidence of CKD. The double role of obesity in the incidence of CKD has also been mentioned in some studies. Conclusions: Such an additional effect arises from the impact of obesity on the incidence of some conditions and diseases such as cardiovascular disease, hypertension, and diabetes, which in turn are involved in the incidence of CKD and are considered as its risk factors.